Alternative payment models and innovation: a case study of US health system adoption of a sacubitril/valsartan to treat acute decompensated heart failure. (1st December 2020) - Shafrin, Jason; Aliyev, Elmar R.; Brauer, Michelle; Park, Siyeon; Shen, Xian
Abstract: Aim: To understand the financial impact of health system adoption of novel heart failure medications under US alternative payment models (APMs). Materials and methods: This study used a decision tree model to assess the financial impact of health system adoption of sacubitril/valsartan to treat acute decompensated heart failure (ADHF). A comparator scenario modeled current health care utilization and cost for treating hospitalized ADHF patients with angiotensin-converting-enzyme inhibitors (ACEi) or angiotensin-receptor blockers (ARB). The study then measured the impact of adopting sacubitril/valsartan to treat ADHF on health system economic outcomes. Differences in treatment efficacy were based on the PIONEER-HF clinical trial. The financial impact of changes in patient outcomes under the sacubitril/valsartan and ACEi/ARB arms was assessed across three APMs: the Medicare Shared Savings Program, Bundled Payments for Care Improvement, and fee-for-service payments adjusted according to the Hospital Readmission Reduction Program. Results: Sacubitril/valsartan reduced re-hospitalizations after an initial ADHF admission by 46.3% for individuals aged 18– 64 years and 23.4% for individuals aged ≥65 years. Health systems' financial benefit of adopting sacubitril/valsartan was $740 per ADHF case per year (PCPY). Savings were larger for patients aged ≥65 years ($803 PCPY) compared to those <65 years ($653 PCPY). The majority of the health system financial benefit came from changes in APM bonus and penalty reimbursements. Value-based payments from the Hospital Readmission Reduction Program ($1, 190 financial gain PCPY) and the Bundled Care Payment Improvement Initiative ($645 financial gain PCPY) produced larger financial benefits than participation in the Medicare Shared Savings Program ($253 financial gain PCPY). Limitations: The model uses clinical trial data, which may not reflect real-world outcomes. Further, the financial implications were modeled based only on three widely used APMs. Conclusion: Sacubitril/valsartan adoption decreased hospitalizations and led to a positive net financial impact on health systems after accounting for APM bonus payments.